Editorial - Mohanty, Bimal Prasanna (Journal of the Inland Fisheries Society of India, 2021)
It’s my great pleasure to present you the second issue of the Vol. 51 of the Journal of the Inland Fisheries Society of India (JIFSI). This issue contains one review/status paper and 12 full research articles. The review paper on ‘Dead Rivers’ of Odisha by Amiya Kumar Sahoo and others is a noteworthy piece of work which highlights present status and scenario of some of the rivers of Odisha which have lost their flow due to geological, ecological factors, etc. This review highlights the prospects of the dead rivers for fisheries development not only in India but also across the world to enhance the shrinking fisheries resources to increase the production and productivity from fisheries and aquaculture. This is necessary for ensuring the food and nutritional security and would contribute in a significant manner towards achieving the Sustainable Development Goals (Goal #2, Zero hunger).